A Case of Ampullary Perforation Treated with a Temporally Covered Metal Stent - Park, Woo Young; Cho, Kwang Bum; Kim, Eun Soo; Park, Kyung Sik (Clinical endoscopy, 2012)
Endoscopic retrograde cholangiopancreatography (ERCP)-related perforation is classified into three or four types based on anatomical location and the mechanism of injury. Although ampullary injury, among them, may be managed nonsurgically, surgical management is required in cases of perforation with retroperitoneal fluid collection and severe condition. Here, a patient with ERCP-related severe ampullary perforation with retroperitoneal fluid collection that was treated nonsurgically with a covered stent is presented.